First isolation and genomic characterization of avian reovirus from black swans (Cygnus atratus) in China - Dekang Zhu; Rong Sun; Mingshu Wang; Renyong Jia; Shun Chen; Mafeng Liu; Xinxin Zhao; Qiao Yang; Ying Wu; Shaqiu Zhang; Juan Huang; Xumin Ou; et al. (Poultry Science, 2023)
ABSTRACT: Identification and analysis of the avian reovirus from black swan.Isolation of the strain through the chorioallantoic membrane route of duck embryos, identified through transmission electron microscopy and RT-PCR based on the ARV S2 gene. The complete genome of the ARV strain was obtained using next-generation sequencing technology.The isolated strain of ARV was named CD200801 and was identified through transmission electron microscopy and RT-PCR based on the ARV S2 gene. Experimental infection with CD200801 resulted in the death of ducklings with serious spleen and liver focal necrosis. BLAST analysis of CD200801 sequences showed a 35.5 to 98.6% similarity to a novel duck reovirus that was isolated in recent years. Phylogenetic analysis revealed that CD200801 was closely related to ARV isolates YL, GX-Y7, and XT-18.We report the first avian reovirus infection in the black swan. This study provides important new insights into the evolutionary relationships among different ARV strains and highlights the need for continued surveillance and monitoring of these viruses in both domestic and wild bird flocks. These findings have significant implications for the development of effective strategies for disease prevention and control in the poultry industry.